Seeming, being and becoming: an intimate, autoethnographic rasa-led performance art exploration - Maharajh, Reshma (University of the Witwatersrand, Johannesburg, 2023)
This thesis focuses on the interplay of "Seeming," "Being," and "Becoming" as it relates to past experiences, present moments and future potentialities. In this project, I delve into the concept of my South African ‘Indianness’ from a personal perspective. As a researcher, I engaged performance art and the aesthetic theory of rasa from the Nātyashāstra a treatise on dramatic theory or the science of drama in Sanskrit (a language of scholarship and philosophy across ancient ‘India’) to explore this concept further. The research encompasses three interconnected practices: rasa, autoethnography, and practice-led research and how central living strategies and concepts are used to define body- mindedness as a life force as emergence in performance strategy. Rasa serves as a guiding metaphor, representing the emotional essence of the artmaking strategies and creative process. These pursuits were not merely cathartic but were about reaching a Transcendental Emotional Moment (TEM) in which "being" and "becoming" converged. Rasa has been proven to be an effective tool in exploring my own identity, subject formation and artmaking, with therapeutic benefits. The second line of inquiry delves into my lived experiences as a widow, mother and practising Hindu, highlighting the complexity of South African Indianness and seeks to bridge the gap between "seeming" and "being" while anticipating what might "become" through the lens of rasa. The third line of inquiry revolves around the practice of performance art (combined with autoethnographic reflection), exploring the tensions between two philosophic models of Integrity and Intimacy as proposed by Kasulis (2002). As the artist (both creator and subject), my life and body became the canvas upon which the artwork unfolded. Performance art allowed for a moment of being when the artwork and I came into existence for each other. This process required cognitive and creative engagement with the project’s content, drawing on past experiences, culture, relationships, politics and religion, guided by rasa. The goal created an environment in which the ‘Oneness of Being’ emerged, leading to a TEM in performance. This moment invited the potential for refreshed, emergent insights and meaning through autoethnography and practice-led research. The “Seeming, Being and Becoming” trajectory and the efficacy of the rasa roadmap is proposed as a cultural philosophy that promotes human flourishing, culminating in the moment of TEM.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; rasa; practice-led research; autoethnography; performance art; body-mindedness; SDG-4: Quality education